Prepaid metering: A way forward for sustainable power sector in Pakistan - Usama Qazi; Shahid Iqbal; Hina Zaheer; Rehman Tauseef Ur (Energy Strategy Reviews, 2020)
Pakistan has been striving for a sustainable power sector for the past two decades. However, the goal has not been achieved yet, due to a long-lasting electricity crisis. This electricity crisis has led to long hours of blackouts, increasing electricity prices, distribution losses, circular debt, and deterioration in the quality of service. This situation requires that we identify the root cause of the electricity crisis that has been an obstacle to the achievement of a sustainable power sector in Pakistan. For that purpose, this research reviewed the power sector of Pakistan over the period 1998–2017. The analysis revealed that the result of catering to the continuously increasing electricity demand under a conventional strategy with unidirectional focus has resulted in a supply-demand deficit, thermally dominated fuel mix, and inefficient recovery. All these issues have undesirable outcomes, with adverse effects on the economy, environment, and social life, resulting in an electricity crisis. Based on this analysis and recent global technological trends, this study proposes the introduction of a prepaid metering system as a practical solution to manage the continuously increasing electricity demand and, hence, the electricity crisis. In the context of Pakistan, this research also identifies administrative, technological, and financial challenges that may affect the smooth implementation of the prepaid metering system and presents policy guidelines to overcome these challenges.